«ГАЛОГЕНЛАР» МАВЗУСИНИ ЎҚИТИШДА ДИДАКТИК МАТЕРИАЛЛАРДАН ФОЙДАЛАНИШ - Ажиева, М.Б.; Кувватова, Г. (SCIENCE and SOCIETY, 2020)
This article describes the use of new didactic materials for teaching halogen subjects.
Keywords: halogen; didactics; chemistry; fluorine; chlorine